Singapore Role in Advancing Global Low-Carbon Economy: A Joint Effort for Sustainability and Climate Commitments - Hossain, Sazib (American Journal of Business Science Philosophy, 2025)
This study examines Singapore’s proactive role in advancing a low-carbon economy by analyzing its policies, innovations, and global partnerships in addressing climate change and promoting sustainability. Despite being a small, densely populated island nation with limited natural resources, Singapore has emerged as a global leader in sustainable development. Its approach integrates forward-thinking policies, cutting-edge technologies, and strategic collaborations. This study employs a structured literature review with a qualitative approach, systematically analyzing key policy documents and case studies of successful initiatives. Initiatives such as the Singapore Green Plan 2030 and the Carbon Pricing Mechanism drive energy efficiency, promote renewable energy adoption, and reduce carbon emissions. Additionally, Singapore actively participates in global climate action, contributing to regional and international platforms. This study highlights Singapore’s efforts in fostering a low carbon economy, encouraging collaboration among policymakers, research institutions, and stakeholders to build a sustainable and resilient global future.